Text altas of wound management - Falanga, Vincent; Lindholm, Christina; Carson, Polly A.; Panuncialman, Jaymie; Mamakos, Lisa; Lotti, Tiziana N.; Falanga, Jane K. (Informa Healthcare, 2012)
The second edition of this critically acclaimed Text Atlas of Wound Management presents new features for dermatologists and nurses who deal with the practical and clinical aspects of wound care. Expert contributors provide a hands-on approach to diagnosis and wound management, as well as a broad exposure to cutaneous wounds-both acute and chronic-to ensure complete exposure to the problems encountered and solutions offered. This colorful guide enables readers to feel as though they are analyzing wounds alongside the experts. With high-quality color illustrations throughout, new highlights include a chapter on histopathology and a section on sourcing products.